2005
DOI: 10.1118/1.1951095
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and validation of three automated methods for measuring ultrasound maximum depth of penetration: Application to ultrasound quality control

Abstract: Systematic measurements of maximum depth of penetration (DOP) of ultrasound (US) scanners are essential for quality control (QC). Conventionally, DOP measurements are performed visually and as such they could be affected by various external factors, scanner control settings, and operator related errors. Automated methods should be free of the issues associated with interoperator dependence and are an attractive alternative to the visual DOP measurements. We implement and test three automated methods for measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 10 publications
(10 reference statements)
0
20
0
Order By: Relevance
“…Because of the subjective nature of this approach, it can be relatively time consuming. We now make routine QC measurements of DOP automatically using custom software to analyze pairs of images, one ''in-air'' with no coupling gel on the transducer and the other of a gel phantom (Gorny et al 2005;Stekel et al 2007). The program determines noise as a function of depth by computing the average value of all pixels at each distance from the transducer face in the in-air image.…”
Section: Maximum Depth Of Penetration (Dop)mentioning
confidence: 99%
“…Because of the subjective nature of this approach, it can be relatively time consuming. We now make routine QC measurements of DOP automatically using custom software to analyze pairs of images, one ''in-air'' with no coupling gel on the transducer and the other of a gel phantom (Gorny et al 2005;Stekel et al 2007). The program determines noise as a function of depth by computing the average value of all pixels at each distance from the transducer face in the in-air image.…”
Section: Maximum Depth Of Penetration (Dop)mentioning
confidence: 99%
“…In scientific literature the maximum depth of ultrasound signal visualization (or penetration depth) is often related to the maximum depth at which echo signals from scattering within a tissue-mimicking phantom can be distinguished from electronic noise [10][11][12][13]. In order to evaluate the parameter above, some theoretical considerations can be done on ultrasound image and characteristic quantities that contribute to propagation of the ultrasound wave in tissues.…”
Section: Maximum Depth Of Ultrasound Signal Visualizationmentioning
confidence: 99%
“…Among technical requirements for an ultrasound diagnostic system a very important role is played by the maximum depth range at which echoes from weakly reflecting scatterers in tissues can be detected above noise, therefore the evaluation of the parameter above is very critical to determine both the diagnostic capabilities and the quality status of the medical system [9]. Nevertheless most of the objective methods for maximum depth of signal visualization measurements are based on noise level estimation [10][11][12][13], that is often not univocally defined for ultrasound imaging. In this work some theoretical considerations on the parameter are illustrated and two methods have been implemented and compared for three diagnostic systems: one of them is developed by the Authors and does not require the noise level estimation.…”
Section: Introductionmentioning
confidence: 99%
“…Thijssen et al reported and implemented a test protocol including a series of quantitative measurements of overall dynamic range, sensitivity, contrast resolution, and spatial resolution 3. Other methods for quantitatively assessing metrics such as resolution integral, depth of penetration (DOP), entropy, correlation, clutter, and spherical target detection have also been proposed 4, 5, 6, 7, 8, 9…”
Section: Introductionmentioning
confidence: 99%